The Role Of Principal Leadership In Improving Teacher Discpline At SMK Islamic Center Cirebon - Hasan, Ali; Mubarok, Ahmad Amin; Novalludin, Wahyu (IAIN Syekh Nurjati Cirebon, 2025)
In this era of rapid and instant development, teacher discipline has experienced a decline. Field observations reveal several challenges related to teacher discipline, such as teacher absenteeism, tardiness, and a lack of motivation in carrying out their duties. Teacher discipline at SMK Islamic Center Cirebon has become a significant issue affecting the effectiveness of the learning process. Problems such as lateness in entering the classroom, absenteeism, and inconsistent task execution remain challenges for the school. This study aims to explore the role of school leadership in improving teacher discipline, examine the current state of teacher discipline, and evaluate the outcomes of the principal's leadership in enhancing teacher discipline at SMK Islamic Center Cirebon. A qualitative descriptive approach with a phenomenological perspective was employed. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the principal's leadership has a significant impact on improving teacher discipline. The principal not only performs administrative functions but also demonstrates exemplary behavior, provides coaching, and implements educational reward and punishment systems. Open communication and regular training further encourage teachers to take greater responsibility. Although some teachers still show irregularities, a culture of discipline has begun to take shape. The principal functions as both a symbolic and participative leader. The strategies implemented have helped foster a professional and conducive work environment. However, teacher discipline has not fully improved due to constraints such as individual character traits and limited direct supervision.